Penerapan Manajemen Risiko Berbasis ISO 31000 Pada UMKM Jasa Les Calistung & Mengaji Rumahan : Studi Kasus Rumah Calistung Ceria - Siska Amelia; Lanina Pratiwi; Ayesa Aulia Sofwa; Shanita Putri Yaperta; Alfiana Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the implementation of ISO 31000–based risk management in a home-based micro tutoring business, with a case study of Rumah Calistung Ceria. This research employs a qualitative descriptive approach through observation, interviews, and simple documentation. The risk management process follows the ISO 31000 framework, including risk identification, risk analysis, risk evaluation, and risk treatment. The results show that the business faces 40 identified risks originating from learning activities, operational processes, human resources, financial aspects, and communication and reputation. Several risks are classified as high and very high, particularly sudden student absences, frequent schedule changes, communication issues with parents, tutor fatigue, and limited learning space. The application of ISO 31000 assists the tutoring business in prioritizing risks and developing structured mitigation strategies, thereby improving service quality, learning safety, communication effectiveness, and long-term business sustainability.